Rhythmus - Balance - Metrum: Formen raumzeitlicher Organisation in den Künsten - Grüny, Christian; Nanni, Matteo (Bielefeld Transcript, 2014)
This volume shows that it is precisely through the interaction of different disciplines that a meaningful concept of spatiotemporal organisation in the arts and beyond can be outlined.At the centre of this is the concept of rhythm, which is important in the various artistic disciplines, but also in history and cultural studies. The contributions explore this in connection with the related concepts of balance and metre, formulating further-reaching theoretical perspectives that are a desideratum even in musicology. (Translated with Deepl.com)
Einleitung / Christian Grüny und Matteo Nanni -- Eine Geschichte der Rhythmen: warum und wie? / Jean-Claude Schmitt -- Die Tücken des Binären, oder warum Gilles Deleuze die Betrachtung des Rhythmus in der Barockmusik aufgegeben hat / Alexander Jakobidze-Gitman -- Kulturen des musikalischen Rhythmus / Steffen A. Schmidt -- Rhythmus und Geste, oder Metaphysics in Mecklenburgh Street / Christian Grüny -- Typen posttonaler Rhythmik / Claus-Steffen Mahnkopf -- Phänodramen oszillierender Membranen / Inge Hinterwaldner -- Henri Matisse, Jazz und der Rhythmus des Lesens / Martin Sundberg -- Rhythmusexperimente – Halt und Bewegung / Christopher Hasty
Keywords: Rhythm; Esthetics